The Role of Peroxisome Proliferator-Activated Receptors in Kidney Diseases - Gao, Jianjun; Gu, Zhaoyan (Frontiers in Pharmacology, 2022)
Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear hormone receptor superfamily of ligand-activated transcription factors. Accumulating evidence suggests that PPARs may play an important role in the pathogenesis of kidney disease. All three members of the PPAR subfamily, PPARα, PPARβ/δ, and PPARγ, have been implicated in many renal pathophysiological conditions, including acute kidney injury, diabetic nephropathy, and chronic kidney disease, among others. Emerging data suggest that PPARs may be potential therapeutic targets for renal disease. This article reviews the physiological roles of PPARs in the kidney and discusses the therapeutic utility of PPAR agonists in the treatment of kidney disease.